Variation in responses to sprint training in male youth athletes: A meta-analysis - Moran, J.; Sandercock, G.; Rumpf, M. C.; Parry, D. A. (International Journal of Sports Medicine, 2017)
The trainability of youths and the existence of periods of accelerated adaptation to training have become key subjects of debate in exercise science. The purpose of this meta-analysis was to characterise youth athletes` adaptability to sprint training across PRE-, MID-, and POST-peak height velocity (PHV) groups. Effect sizes were calculated as a measure of straight-line sprinting performance with studies qualifying based on the following criteria: (a) healthy male athletes who were engaged in organised sports; (b) groups of participants with a mean age between 10 and 18 years; (c) sprint training intervention duration between 4 and 16 weeks. Standardised mean differences showed sprint training to be moderately effective (Effect size=1.01, 95% confidence interval: 0.43-1.59) with adaptive responses being of large and moderate magnitude in the POST- (ES=1.39; 0.32-2.46) and MID- (ES=1.15; 0.40-1.9) PHV groups respectively. A negative effect size was found in the PRE group (ES=-0.18; -1.35-0.99). Youth training practitioners should prescribe sprint training modalities based on biological maturation status. Twice weekly training sessions should comprise up to 16 sprints of around 20 m with a work-to-rest ratio of 1:25 or greater than 90?s.